Spleen stiffness to liver stiffness ratio significantly differs between ALD and HCV and predicts disease-specific complications - Elshaarawy, Omar; Müller, Johannes; Guha, Indra Neil; Chalmers, Jane; Harris, Rebecca; Krag, Aleksander; Madsen, Bjørn Stæhr; Stefanescu, Horia; Farcau, Oana; Ardelean, Andreea; Procopet, Bogdan; Thiele, Maja; et al. (JHEP reports, 2019)
Background & Aims - Both liver stiffness (LS) and spleen stiffness (SS) are widely used to non-invasively assess liver fibrosis and portal hypertension, respectively. We aimed to identify the impact of disease etiology, namely the localization of inflammation (portal vs. lobular), on the SS/LS ratio. - Methods - In this multicenter study, LS and SS were prospectively assessed in 411 patients with alcohol-related liver disease (ALD) or hepatitis C virus (HCV) using FibroScan® (Echosens, Paris); changes in these parameters were also studied in response to treatment (alcohol withdrawal, HCV therapy). LS and spleen length (SL) were further analyzed in a retrospective cohort of 449 patients with long-term data on decompensation/death. - Results - Both, SS and SL were significantly higher in HCV compared to ALD (42.0 vs. 32.6 kPa, p≪0.0001, 15.6 vs. 11.9 cm, p≪0.0001) despite a lower mean LS in HCV. Consequently, the SS to LS ratio and the SL to LS ratio were significantly higher in HCV (3.8 vs. 1.72 and 1.46 vs. 0.86, p≪0.0001) through all fibrosis stages. Notably, SL linearly increased with SS and the relation between SS and SL was identical in HCV and ALD. In contrast, livers were much larger in ALD at comparable LS. After treatment, LS significantly decreased in both diseases without significant changes to the SS/LS ratio. In the prognostic cohort, patients with ALD had higher LS values (30.5 vs. 21.3 kPa) and predominantly presented with jaundice (65.2%); liver failure was the major cause of death (p≪0.01). In contrast, in HCV, spleens were larger (17.6 vs. 12.1 cm) while variceal bleeding was the major cause of decompensation (73.2%) and death (p≪0.001). - Conclusion - Both SS/LS and SL/LS ratios are significantly higher in patients with portal HCV compared to lobular ALD. Thus, combined LS and SS or SL measurements provide additional information about disease etiology and disease-specific complications. - Lay summary - Herein, we show that patients with hepatitis C virus infection (HCV) have higher spleen stiffness and portal pressure than patients with alcohol-related liver disease (ALD), within the same fibrosis stage and matched to liver stiffness. Thus, the spleen stiffness to liver stiffness ratio is significantly higher in patients with HCV compared to ALD. Additionally, patients with HCV more commonly progress to portal hypertension-related complications (e.g. variceal bleeding), while patients with ALD more commonly progress to liver failure (e.g. jaundice). The spleen stiffness to liver stiffness ratio is a useful tool to confirm disease etiology and predict disease-specific complications.